Inscription, David Sassoon Clock Tower - Ghosh, Ayan (2023)
David Sassoon's (1792–1864) name is inscribed on the ground floor arch. He funded many public welfare institutions and also donated £15,000 for the construction of an illuminated clock tower at the entrance to Victoria Gardens. Various charity trusts, which continue to exist today, were funded and named after David Sassoon and members of the Sassoon family.